ENVIRONMENTAL SAFETY IN THE FERGANA REGION: PROBLEMS, MONITORING, AND MANAGEMENT MECHANISMS - Urinbayeva Dilyora Khamzayevna (Ecominds Press, 2025)
This article analyzes the existing challenges related to ensuring environmental safety in the Fergana region, the current state of environmental monitoring, and the effectiveness of ecological management mechanisms. It examines air, water, and soil pollution in the region, waste management issues, the impact of technogenic processes, and factors associated with climate change. The study also discusses environmental policies implemented to strengthen ecological safety, the introduction of green technologies, digital monitoring systems, and sustainable management strategies aimed at improving regional environmental stability.
Keywords: Environmental safety, monitoring, natural resources, air pollution, water quality, waste management, sustainable development, green technologies, environmental policy.